PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI DAN INFORMASI DI SDI PLUS HIDAYATUT THOLIBIN KABUPATEN KEDIRI - Fatma Dewi, Ardiana; Anggi Maiyanti, Aziza; Anggraini, Atika; Yusal , Yulianti (Proceedings of Annual Conference on Community Engagement, 2024)
Learning as a process of interaction between teachers and other learning resources needs to be supported by the use of appropriate media. The development of learning media has often been carried out by educators along with the times and technology. One of them is the development of technology and information-based learning media. One of the learning media used is Microsoft Power Point, based on previous research the PowerPoint-based learning media developed is valid and effective. So that in this community service, training was carried out for the development of technology and information-based learning media using Microsoft Power Point which was carried out at SDI Plus Hidayatut Tholibin, Kediri Regency. Thus this training can be utilized by teachers at SDI Hidayatut Tholibin to develop competence as an educator and implement it in a real way to create more effective teaching activities with maximum student learning outcomes.